2015
DOI: 10.1007/s00520-014-2549-9
|View full text |Cite
|
Sign up to set email alerts
|

Design, development, and feasibility of a spanish-language cancer survivor support group

Abstract: Purpose Latino cancer survivors experience lower psychosocial well-being compared to Non-Latino Whites. This study describes the development of a culturally-appropriate support group and reports on feasibility of implementation and preliminary outcomes. Methods Promotores (lay health workers) conducted all aspects of data collection and program implementation. Participants were 29 Spanish-speaking Latino cancer survivors (n=12 men, 17 women) who took part in one of three study phases. Phase 1 included one-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 33 publications
(41 reference statements)
0
37
0
Order By: Relevance
“…A bridge person is identified as, for instance, a same-cultural researcher, a (trained) community member or leader, or a member of staff from a community-based organization. A shared (cultural) identity and core values help to build trust, as, noted, for example, by Ceballos et al ([ 20 ], p. 2146): “ Through their often long-standing and trusted relationships with communities, promotores provide a familiarity often unattainable by researchers, especially among underserved communities.”.…”
Section: Resultsmentioning
confidence: 99%
“…A bridge person is identified as, for instance, a same-cultural researcher, a (trained) community member or leader, or a member of staff from a community-based organization. A shared (cultural) identity and core values help to build trust, as, noted, for example, by Ceballos et al ([ 20 ], p. 2146): “ Through their often long-standing and trusted relationships with communities, promotores provide a familiarity often unattainable by researchers, especially among underserved communities.”.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reviewed included participants who could be difficult to recruit: busy professionals (Baillie et al 2016;Robinson et al 2012); mothers with young babies (Carroll et al 2014;Hunter and Magill-Cuerden 2014); and minority ethnic groups, who required interpreters (Ceballos et al 2015;Riggs et al 2015). Researchers adopted a flexible approach to include particular individuals in their samples, potentially enriching the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarises the studies identified, with topic, methodologies and numbers of focus groups and interviews. Only one study included a theoretical rationale for use of focus groups (Ceballos et al 2015), referring to interactions and referenced to Kitzinger (1994). No studies included discussions about how the interview data differed from the focus group data.…”
Section: Exchanging or Adding Individual Interviews Into Studies Desimentioning
confidence: 99%
“…These included translation of materials, incorporation of culturally relevant features (eg, exercise and traditional foods), and inclusion of hands‐on activities, which are often integrated into cultural adaptations of behavioral health interventions . We also added education regarding sexuality, health insurance, spirituality, patient‐provider communication, employment, and finances; Latino/a survivors have expressed interest in these topics in previous studies . While Latino/as often value having a personal relationship with their doctors, many in the United States describe feeling more distant to medical professionals and therefore often seek less care .…”
Section: Discussionmentioning
confidence: 99%